Brinjal – Thar Rachit for cultivation under hot arid agro-climate - Samadia, D K; Haldhar, S M; Verma, A K; Saroj, P L (Indian Horticulture, 2019)
Brinjal is indigenous and most accepted vegetable crop for year-round production but it fruits has regional preferences for size, shape, colour and quality attributes. On evaluation of wide range of germplasm, brinjal genotypes from favourable agro-climatic zones did not perform well under high temperature and abiotic stressed conditions of hot arid region. Therefore, promotion of varieties from native genetic resource is beneficial and in that direction ICAR–CIAH, Bikaner has developed and recommended Thar Rachit for commercial cultivation under resource poor arid environment. It is very early in first harvesting and takes 45 days from transplanting. It is prolific bearer (79.5–92.3 fruits) and marketable yield is 3.16–4.35 kg/plant. Grade A fruits at marketable stages are oblong-round, small, dark purple and 39.8– 46.2 g in weight.